1999
DOI: 10.1086/314961
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of TT Virus Viremia in Italian Patients, Regardless of Age, Clinical Diagnosis, and Previous Interferon Treatment

Abstract: The pathogenic potential of the newly discovered TT virus (TTV) is currently a matter of conjecture. Its presence was investigated in the serum of 660 patients, by polymerase chain reaction. TTV was detected in 50% of 221 patients with unselected pathologies, and no significant differences related to age, sex, or organ disease were noted. TTV was present at a significantly higher rate in hemophiliacs (73%) and at lower rates in patients with cirrhosis (30%) and rheumatoid arthritis (28%). Patients with other l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
34
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 14 publications
(30 reference statements)
11
34
1
Order By: Relevance
“…At day 90, the mean TTV load was slightly increased relative to that at day 30, although the increase did not reach statistical significance. Table 1 also shows that in the same patients, baseline levels and responses to treatment of HCV were in line with published data (3,12,19). A substantial decline in mean HCV viremia was clearly evident at day 1 of treatment, when one patient was already below the assay sensitivity limit (3 log 10 copies/ml).…”
Section: Resultssupporting
confidence: 87%
“…At day 90, the mean TTV load was slightly increased relative to that at day 30, although the increase did not reach statistical significance. Table 1 also shows that in the same patients, baseline levels and responses to treatment of HCV were in line with published data (3,12,19). A substantial decline in mean HCV viremia was clearly evident at day 1 of treatment, when one patient was already below the assay sensitivity limit (3 log 10 copies/ml).…”
Section: Resultssupporting
confidence: 87%
“…At the same time, epidemiological associations of TTV with B-cell lymphoma, Hodgkin's disease, aplastic anemia, idiopathic pulmonary fibrosis, acute respiratory disease, and autoimmune rheumatic disorders have also been described (6,16,29,30,32,52). Although TTV is potentially related to many diseases, its actual function is still questioned.…”
mentioning
confidence: 99%
“…Viremic hemophiliacs had increased levels of IgG and IgM in serum relative to TTV-negative hemophiliacs (187). Maggi et al (90) found that infection rates in patients with psoriasis, rheumatoid arthritis, or systemic lupus erythematosus were not higher than in patients with miscellaneous diseases. In another study, viremic patients with rheumatoid arthritis had a greatly enhanced frequency of rheumatoid factor positivity (54).…”
Section: Clinical Significancementioning
confidence: 99%